Inorganic arsenic promotes luminal to basal transition and metastasis of breast cancer. Issue 12 (13th October 2020) - Danes, Jeanne M.; de Abreu, Andre L. P.; Kerketta, Romica; Huang, Yunping; Palma, Flavio R.; Gantner, Benjamin N.; Mathison, Angela J.; Urrutia, Raul A.; Bonini, Marcelo G.
Abstract: Inorganic arsenic (iAs/As2 O3 2− ) is an environmental toxicant found in watersheds around the world including in densely populated areas. iAs is a class I carcinogen known to target the skin, lungs, bladder, and digestive organs, but its role as a primary breast carcinogen remains controversial. Here, we examined a different possibility: that exposure to iAs promotes the transition of well‐differentiated epithelial breast cancer cells characterized by estrogen and progesterone receptor expression (ER+/PR+), to more basal phenotypes characterized by active proliferation, and propensity to metastasis in vivo. Our results indicate two clear phenotypic responses to low‐level iAs that depend on the duration of the exposure. Short‐term pulses of iAs activate ER signaling, consistent with its reported pseudo‐estrogen activity, but longer‐term, chronic treatments for over 6 months suppresses both ER and PR expression and signaling. In fact, washout of these chronically exposed cells for up to 1 month failed to fully reverse the transcriptional and phenotypic effects of prolonged treatments, indicating durable changes in cellular physiologic identity. RNA‐seq studies found that chronic iAs drives the transition toward more basal phenotypes characterized by impaired hormone receptor signaling despite the conservation of estrogen receptor expression. Because treatments for breast cancer patients are largely designed based on the detection of hormone receptor expression, our results suggest greater scrutiny of ER+ cancers in patients exposed to iAs, because these tumors may spawn more aggressive phenotypes than unexposed ER+ tumors, in particular, basal subtypes that tend to develop therapy resistance and metastasis.